The Impact of Cross-Cultural Learning on Islamic Religious Identity among Muslim Students Abroad - Khaled Abdelhay Elsayed; Sabri Mohamad; Kafieh Khojasteh Mah Sayeh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the impact of cross-cultural learning experiences on the formation and transformation of Islamic religious identity among Muslim students studying abroad. It explores how exposure to multicultural educational settings influences their faith, behavior, and understanding of Islam. Methodology: This research employed a qualitative descriptive approach with a phenomenological design to examine the lived experiences of 15 Muslim students from Indonesia, Malaysia, and Pakistan studying in Turkey and Malaysia. Data were collected through semi-structured interviews, observations, and reflective journals, and analyzed thematically using Braun and Clarke’s six-step framework. Main Findings: The results show that cross-cultural learning strengthens students’ religious identity through five main processes: reflective faith development, adaptive worship practices, intercultural dialogue, community-based support, and the emergence of a global Muslim identity. Students demonstrated spiritual resilience, deeper religious understanding, and intercultural competence while maintaining Islamic values in pluralistic environments. Novelty/Originality of this study: This study introduces a holistic framework linking cross-cultural learning with Islamic religious identity formation. It highlights the role of intercultural engagement as a form of reflective religiosity that strengthens faith through dialogue and adaptation. The findings advance the field of Islamic education by positioning cross-cultural experience as a pedagogical model for fostering wasatiyyah, resilience, and global Muslim consciousness.